The aryl hydrocarbon receptor in liver injury: a double-edged sword in roles, mechanisms, and future perspectives - Wang, Yupeng; Ren, Tianqi; Zhang, Yikun; Li, Shuangxing; Yang, Yanwei; Wang, Chao; Geng, Xingchao (Frontiers in Pharmacology, 2026)
The aryl hydrocarbon receptor (AhR) is a key regulatory factor that enables the organism to sense and integrate environmental and metabolic signals. Its biological function exhibits a universal “dual nature,” a feature that has been relatively well studied in organs such as the skin, lungs, and intestines. However, in the pathological processes of the liver—the central metabolic organ—the specific molecular mechanisms and regulatory networks that determine the functional orientation of AhR (whether protective or detrimental) remain a frontier and highly controversial area of research. This review aims to critically synthesize existing evidence, elucidating how AhR influences the progression of liver injury by regulating apoptosis, stress-induced damage, metabolic homeostasis, autophagy, fibrosis, and tumor development. It further explores the causes of its functional heterogeneity, such as ligand specificity and tissue microenvironment. By analyzing current controversies and cognitive gaps in the field, this article seeks to provide a framework for clarifying the complex role of AhR in liver diseases and to guide future exploration of targeted intervention strategies.